PENGELOLAAN SISTEM PENDIDIKAN DI MADRASAH IBTIDAIYAH SWASTA AL IKHWAN BUKITTINGGI DENGAN MANAJEMEN BERBASIS KINERJA - Basit, Abdul; Besral, Besral; Huda, Muhammad Jamalul (UIN Imam Bonjol Padang, 2024)
Educational performance-based strategicmanagement canbe said tobe a process of planning,measuring,assessingandevaluatingpersonnelperformancetorealizeeducational goalsandoptimizepersonalpotential.Theroleof theheadofMISAlIkhwanBukittinggi isof courserequiredtobeabletomanagetheexistingeducationsystemintheMadrasah well. This researchaims to findout howthe strategyof theheadofMISAl Ikhwan Bukittinggimanagesperformance-basedmanagementof existingpersonnel.Theresearch method used in this research is descriptive qualitative research using interview and observationdataanalysismethods.Theresultsof this researchshowthatmadrasaheads manage performance-basedmanagement using a systemof recruitment, orientation, empowermentandorganization, compensation,developmentandtraining, evaluationand dismissal. Through this system, themadrasa head is objectively proven tobe able to managetheeducationsysteminthemadrasawell,produceoptimaleducation,andfindthe rightsolutionsandworkprograms.